Knowledge and waste management based on local wisdom on environmental health complaints - Ardhianingrum, Galuh Saraesti; Deismawaranti, Asri; Siwidati, Anggit Wirama; Puarada, Sabil Agung Bestari; Mulyani, Dwi (BKM Public Health and Community Medicine, 2025)
Objective: This study explores environmental health issues related to waste management, focusing on the local wisdom that makes biopore holes to accommodate organic waste with Budaya Gawe Jugangan Sampah Organik as known as ”BYGJUSO”, to understand the relationship between knowledge and waste management based on local wisdom and public health complaints. Methods: The study used a cross-sectional approach. It was conducted in October 2024 in Sorogenen Village, RT 34, RW 09, Sorosutan, Umbulharjo, Yogyakarta City. The sample consisted of 30 family Empowerment and Welfare (PKK) members, selected through purposive sampling. The data were analyzed using univariate analysis, including cross-tabulation, and bivariate analysis with Fisher’s exact test. Results: The statistical analysis revealed a p-value of 0.037 for the association between the edge and environmental health complaints, indicating a significant relationship. In contrast, the p-value for the association between waste management and environmental health complaints was 0.491, indicating no statistically significant relationship. Conclusion: These results suggest that enhancing environmental knowledge may play a crucial role in addressing public health concerns, whereas waste management practices alone may not have a direct influence on health complaints.